2014
DOI: 10.1007/s10397-014-0865-1
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy findings and its correlation with latent endometrial tuberculosis in infertility

Abstract: In India, 5 to 18 % of females attending infertility clinics are diagnosed to be suffering from genital tuberculosis. The present study was conducted to find out the prevalence of endometrial tuberculosis in infertility and its correlation with hysteroscopic changes. Patients attending infertility clinic with history of more than 2 years of unexplained infertility, failure to conceive in spite of successful ovulation induction in anovulatory infertility, and secondary infertility with a history of unexplained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…(6,9) Several observations made during laparoscopy and hysteroscopy have been mentioned in the published research relevant to FGTB. (6,(10)(11)(12). In addition, treatment with anti-tubercular medication is started once that has been determined to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…(6,9) Several observations made during laparoscopy and hysteroscopy have been mentioned in the published research relevant to FGTB. (6,(10)(11)(12). In addition, treatment with anti-tubercular medication is started once that has been determined to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Several observations made during laparoscopy and hysteroscopy have been mentioned in the published research that are relevant to FGTB. [14][15][16][17] This pioneering study explores uncharted territory, delving into laparoscopic and hysteroscopic findings in subfertile women with confirmed FGTB. It seeks to illuminate the diagnostic prowess of these procedures, unveiling tuberculosis-related anatomic and physiological shifts while enhancing diagnostic precision and patient well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Several observations made during laparoscopy and hysteroscopy have been mentioned in the published research that are relevant to FGTB 14–17 . This pioneering study explores uncharted territory, delving into laparoscopic and hysteroscopic findings in subfertile women with confirmed FGTB.…”
Section: Introductionmentioning
confidence: 99%
“…1 The two-third of this global burden presented in eight countries included; India, Indonesia, China, the Philippines, Pakistan, Nigeria, Bangladesh, and South Africa. 1 Female Genital Tuberculosis is commonly secondary to pulmonary TB (PTB) or extrapulmonary TB (EPTB), with the incidence rate ranging between 9 to 20 and 5 to 13 among overall EPTB, 2,3 and PTB, 4,5 cases worldwide 6 , respectively. Typically female genital Tuberculosis (FGTB) is known as the disease of young women (20-40 year-old) 5,7 , and it is usually diagnosed during infertility evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…1 Female Genital Tuberculosis is commonly secondary to pulmonary TB (PTB) or extrapulmonary TB (EPTB), with the incidence rate ranging between 9 to 20 and 5 to 13 among overall EPTB, 2,3 and PTB, 4,5 cases worldwide 6 , respectively. Typically female genital Tuberculosis (FGTB) is known as the disease of young women (20-40 year-old) 5,7 , and it is usually diagnosed during infertility evaluations. 2,8 A previous study indicated that the infertility rates in women is higher compared to men 9 .…”
Section: Introductionmentioning
confidence: 99%